A moderate zinc deficiency does not impair gene expression of PPARalpha, PPARgamma, and mitochondrial enoyl-CoA delta isomerase in the liver of growing rats - Justus, Jennifer; Weigand, Edgar; Justus Liebig University Giessen (My University, 2014)
The aim of the study was to investigate the impact of a moderate zinc deficiency and a high intake of polyunsaturated fat on the mRNA expression of peroxisome-proliferator-activated receptor alpha (PPARalpha), peroxisome-proliferator-activated receptor gamma (PPARgamma), and mitochondrial delta 3delta2-enoyl-CoA isomerase (ECI) in the liver. Weanling rats were assigned to five groups (eight animals each) and fed semi-synthetic, low-carbohydrate diets containing 7 or 50 mg Zn/kg (low-Zn (LZ) or high-Zn (HZ)) and 22% cocoa butter (CB) or 22% safflower (SF) oil for four weeks. One group each was fed the LZ-CB, LZ-SF, or HZ-SF diet free choice, and one group each was fed the HZ-CB and HZ-SF diets in restricted amounts according to intake of the respective LZ diets. The LZ diets markedly lowered growth and zinc concentrations in plasma and femur. Hepatic mRNA levels of PPARalpha, PPARgamma, and ECI were not reduced by the moderate zinc deficiency. Overall, ECI-mRNA abundance was marginally higher in the SF-fed than in the CB-fed animals.
Keywords: zinc deficiency; PPARalpha; PPARgamma; enoyl-CoA isomerase; cocoa butter; ddc:630